2020
DOI: 10.15625/1811-4989/16/4/8866
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of natural compounds from sponge – derived fungus Aspergillus flocculosus 01NT.1.1.5

Abstract: The Aspergillus fungi have been an important source of natural products that are useful for exploration in medicine, agriculture and industry. In our continuous investigation to search for new antimicrobial agents from marine-derived fungi, one new phomaligol A2 (1), together with three known compounds, wasabidienone E (2), aspertetranone D (3) and mactanamide (4), were obtained from the EtOAc extract of the culture medium of the marine-derived fungus Aspergillus flocculosus (A. flocculosus) 01NT.1.1.5 isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The revised structure of ring B is closely similar to that of sarcosone derivatives, which are common fungal polyketides containing a 3-methoxycyclohexenone ring as a substructure, and we have isolated several 3-methoxycyclohexenone analogues from the same strain. , Therefore, we compared the chemical shifts of the revised structure of ring B and 3-methoxycyclohexenone derivatives and found that they are well matched to each other (Figure S19). Moreover, the UV spectrum of 1 (Figure S27) displayed a strong absorption peak at 256 nm, which was similar to that of other 3-methoxycyclohexenones, and the IR spectrum (Figure S28) showed an absorption band at 1643 cm –1 corresponding to an α,β-conjugated carbonyl as in the revised structure (unconjugated carbonyl as in the proposed structure absorbs at >1700 cm –1 ). , Additionally, an extensive literature review revealed that the chemical shift of the methyl group in methyl esters of glucuronic acid (similar to the proposed structure) is smaller than 53 ppm (δ C 51–53) (Table S2).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The revised structure of ring B is closely similar to that of sarcosone derivatives, which are common fungal polyketides containing a 3-methoxycyclohexenone ring as a substructure, and we have isolated several 3-methoxycyclohexenone analogues from the same strain. , Therefore, we compared the chemical shifts of the revised structure of ring B and 3-methoxycyclohexenone derivatives and found that they are well matched to each other (Figure S19). Moreover, the UV spectrum of 1 (Figure S27) displayed a strong absorption peak at 256 nm, which was similar to that of other 3-methoxycyclohexenones, and the IR spectrum (Figure S28) showed an absorption band at 1643 cm –1 corresponding to an α,β-conjugated carbonyl as in the revised structure (unconjugated carbonyl as in the proposed structure absorbs at >1700 cm –1 ). , Additionally, an extensive literature review revealed that the chemical shift of the methyl group in methyl esters of glucuronic acid (similar to the proposed structure) is smaller than 53 ppm (δ C 51–53) (Table S2).…”
mentioning
confidence: 66%
“…During the course of our ongoing research for novel marine natural products, we have isolated a number of oxygenated cyclohexenone derivatives from two strains of Aspergillus flocculosus , 01NT-1.1.5 and 168ST-16.1. Among them, compound 1 was isolated as a pure compound with identical 1D and 2D NMR data to those of asperspiropene A. However, the HRESIMS data of 1 were different from the previously published data for asperspiropene A. Additionally, we found that some 2D NMR data of asperspiropene A (COSY and HMBC) were incorrectly interpreted .…”
mentioning
confidence: 77%
“…01NT-1.1.5 grown on rice medium led to the isolation of fungal metabolites having antimicrobial properties and the suppression of RANKL-induced osteoclastogenesis activities [4,5]. To further study the secondary metabolites from marine-derived fungi, the "one strain many compounds" (OSMAC) strategy was applied by changing the culture medium from rice medium to Bennett's broth medium.…”
Section: Introductionmentioning
confidence: 99%
“…As part of our ongoing program to investigate marine-derived fungi as an underexplored source of new natural products, we focused our attention on Aspergillus unguis 158SC-067 and A. flocculosus 01NT-1.1.5 strains, which showed good antimicrobial activity in the preliminary screening. Our previous studies on the EtOAc extract of A. flocculosus 01NT-1.1.5 grown on rice medium led to the isolation of fungal metabolites having antimicrobial properties and the suppression of RANKL-induced osteoclastogenesis activities [ 4 , 5 ]. To further study the secondary metabolites from marine-derived fungi, the “one strain many compounds” (OSMAC) strategy was applied by changing the culture medium from rice medium to Bennett’s broth medium.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to studies on sponge taxonomy and sponge-derived natural products, Vietnamese sponge-associated microbiota and their natural products remain largely unexplored and have only been studied in the last few years. These studies focused on the isolation of spongeassociated microbes that produce bioactive compounds (Trinh et al, 2016;Cao et al, 2019;Cao et al, 2020;Quang et al, 2020;Trinh et al, 2020;Chau et al, 2021;Quang et al, 2021a;Kim et al, 2022;Phan et al, 2022;Trinh et al, 2022). Interestingly, several new antimicrobial and cytotoxic compounds have been isolated successfully from Vietnamese sponge-associated microbes (Cao et al, 2019;Cao et al, 2020;Trinh et al, 2020;Quang et al, 2021a;Kim et al, 2022;Trinh et al, 2022), revealing that microbes associated with Vietnamese sponges may be a promising source of new bioactive compounds.…”
Section: Studies In Sponges and Sponge-associated Microorganisms In V...mentioning
confidence: 99%